Statistical optimization of process conditions for cellulase production by liquid state bioconversion of domestic wastewater sludge - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Wahid, Rosmaziah (Elsevier, 2008)
A two-level fractional factorial design (FFD) was used to determine the effects of six factors, i.e. substrate (domestic wastewater sludge – DWS) and co-substrate concentration (wheat flour – WF), temperature, initial pH, inoculum size and agitation rate on the production of cellulase enzyme by Trichoderma harzianum in liquid state bioconversion. On statistical analysis of the results from the experimental studies, optimum process conditions were found to be temperature 32.5 C, substrate concentration (DWS) 0.75% (w/w), co-substrate (WF) concentration 2% (w/w), initial pH 5, inoculum size 2% (v/w) and agitation 175 rpm. Analysis of variance (ANOVA) showed a high coefficient of determination (R2) of 0.975. Cellulase activity reached 10.2 FPU/ml at day 3 during the fermentation process which indicated about 1.5-fold increase in production compared to the cellulase activity obtained from the results of design of experiment (6.9 FPU/ml). Biodegradation of DWS was also evaluated to verify the efficiency of the bioconversion process as a waste management method.